Badmen, bandits, and folk heroes : the ambivalence of Mexican American identity in literature and film - Alonzo, Juan J. (Juan José), 1969- (The University of Arizona Press, 2009)
"Badmen, Bandits, and Folk Heroes is a comparative study of the literary and cinematic representation of Mexican American masculine identity from early-twentieth-century adventure stories and movie Westerns through contemporary self-representations by Chicano/a writers and filmmakers"--Jacket